Penguatan Kompetensi Guru dalam Mendesain Asesmen Pembelajaran Matematika melalui Program Pendampingan - Sudianto, Sudianto; Santoso, Erik; Mahmudin, Dede (SANISKALA : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to improve the understanding and skills of mathematics teachers in designing effective assessments that align with learning objectives. The training was conducted in collaboration with the Subject Teachers' Working Group (MGMP) for Junior High School Mathematics in Majalengka Regency on May 21, 2025. The training materials covered an understanding of formative, summative, and diagnostic assessments, as well as practical exercises in constructing questions based on Bloom-Anderson’s taxonomy. The implementation methods included interactive lectures, group discussions, and assessment design simulations. Evaluation was carried out using pre-tests and post-tests with a semantic differential scale. The analysis results showed a significant increase in participants’ understanding of the concepts and importance of assessment in mathematics learning. Before the training, most participants were at a moderate skill level, while after the training, there was a shift toward a higher skill level. These findings indicate that the training effectively improved teachers’ competencies. This activity is expected to be the first step in strengthening teachers’ capacity to design assessments that support meaningful learning in the classroom.